2018
DOI: 10.1007/s11657-018-0550-5
|View full text |Cite
|
Sign up to set email alerts
|

The consistency of care for older patients with a hip fracture: are the results of the integrated orthogeriatric treatment model of the Centre of Geriatric Traumatology consistent 10 years after implementation?

Abstract: In the past 10 years after implementation, the orthogeriatric treatment model led in general to consistent outcomes for 1555 older adults in terms of most of the complications and mortality. Surgery was more often delayed to 24-48 h after arrival at the hospital, while the length of hospital stay shortened. Introduction Since 1 April 2008, patients aged ≥ 70 years presenting themselves with a hip fracture at Ziekenhuisgroep Twente (ZGT) have been treated according to the orthogeriatric treatment model. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…A standardised care often uses principles from lean methodology [5] to improve patient outcomes and hospital efficiency, leading to decreased hospital length of stay (LOS) [6] . A standardised care for patients with a hip fracture at our hospital led to a reduction of 3.4 days in LOS, with no increase in mortality or readmission [7] , consistent with other studies [8][9][10][11] . A reduction in LOS may counter the increased demand for hospital care and expanding costs [12] .…”
Section: Introductionsupporting
confidence: 89%
“…A standardised care often uses principles from lean methodology [5] to improve patient outcomes and hospital efficiency, leading to decreased hospital length of stay (LOS) [6] . A standardised care for patients with a hip fracture at our hospital led to a reduction of 3.4 days in LOS, with no increase in mortality or readmission [7] , consistent with other studies [8][9][10][11] . A reduction in LOS may counter the increased demand for hospital care and expanding costs [12] .…”
Section: Introductionsupporting
confidence: 89%
“…Studies have shown that at the 6 month mark following surgery for hip fractures only 50% of the patients were able to regain independence with activities of daily living(ADL). 2,3 The 1-year mortality for hip fractures ranges from 8.4% to 36%. This imposes a heavy burden on the health care system as well as the community.…”
Section: Introductionmentioning
confidence: 99%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis ( Figure and eAppendix 3 in the Supplement ). 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%